A Story Does Exist: A Qualitative Exploration of the Use of Reflective Stories in Pre-Practicum. Issue 3 (3rd July 2017) - Duffy, Jason T.; Saltis, Michelle N.; Thompson, Laura K.; Kassirer, Steven J.
ABSTRACT: The authors explored the lived experiences of two cohorts of counselors-in-training who experienced a metaphoric story creation activity in pre-practicum II, a clinical training course. Using Merriam's interpretive qualitative approach, the data suggested that students perceived the activity to have facilitated their ability to make meaning of their experiences in the class, as well as to better understand their development as counselors-in-training.